President and parliament: Influence on the stability of the state - Talat-Kelpša, Laimonas (Politologija, 1997)
In this article Talat-Kelpša attempts to depict a motley picture concerning the impact that the interinstitutional relations of the president and the parliament derive in the process of establishing a politically stable state and applies an attractive structural development of this clarified problem.The author employs a method of research where the chronological aspect is of peculiar concern. By the same token, he shows how different governmental institutions lost or derived influence on each other due to what he terms as "formal" and "informal" processes (conditions). Constitutional separation of the branches of government acts as "formal," and subsequent (following this prior act) procedural and behavioral participation on the political arena, accomplishment of the duties assigned, incarnates "informal" processes. These two processes shape power and magnitude of some single institution.The author inevitably produces certain conclusions that are of great interest: "semi-presidentialism gives incentives to bipolar tendencies, which, due to Lithuania's experience, acting with the back-up of a mixed electoral system, may certainly produce an absolute one-party majority." But primarily, we are introduced to the theoretical analysis of the four models of the semi-presidential regime—the one, as the author claims, that Lithuania naturally adopted under the Constitution of 1992. In addition, we can find concise but accurate interpretations and comments on any of these shifts had, has, or might probably have to the political stability of Lithuania. Consequently, four types of the semi-presidential regime (the author intercepted them from A. Stepan and E. N. Suleiman) appear to be defined in the first part of the article.Further on, the author ascertains that Lithuania has already experienced three (out of four) types of the mentioned models. He emphasizes that in the period of 1993-1996, Lithuania fitted the model of presidential majority best. Elections of Seimas, 1996, witnessed the imposition of the new model—the one of "coexistence." February events, 1996, disclosed a momentary appearance of the third script (when the presidential majority betrays the president and supports the Prime Minister).Interesting remarks seem to appear in the study: the passive role that Brazauskas used to play in the field of domestic policy, his non-intervenance, has set a fruitful basement to the emergence of a stereotypically understood image of the president who is now primarily understood as the passive and the "good" one. Thus, the author argues that such a situation created a precedent. Future keen presidents should have additional complexities in attaining public support and overriding parliamentary resistance.The second part of the article offers a deep insight into the sources that condition conflictuality in the model of "coexistence." In accordance with F. W. Rüb's classification of these sources, the author ascertains several means the president should employ or would otherwise become symbolic. All the four sources authorize indispensable influence and direct threat to the political stability of the country where passiveness and non-establishment of the limits of competence favor parliamentary dominance.Conclusively, it must be said that this article picturing the role both president and parliament play in determining the state of political stability is exceptionally favorable.
Keywords: -